Nurse in maternity ward, using Beckman Model D oxygen analyzer to monitor an infant in an incubator - Preston E. Mitchell Commercial Photography (1960)
Los Angeles County General Hospital nurse Mary Finlay is monitoring the oxygen levels of a prematurely born infant in an incubator, to provide just the right oxygen mixture. Too little oxygen has obvious repercussions, but until the 1950s doctors did not realize that too much oxygen caused retrolental fibroplasia, resulting in blindness. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Los Angeles County General Hospital; Newborn infants; Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Nurses; Beckman Instruments, Inc.